An interactive knowledge based recommender system for tourism - Ahmed, Wakil; Nur, Farah; Hema, Nabila Bhuyan; Ahmed, Nasim (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2017.